Teaching Grammar Using Mind Maps (matn Al-ajrumiyyah As A Model) - khaloui, soumicha (El Omda in Linguistics and Discourse Analysis, 2022)
Grammar is one of the basics of understanding the Arabic language, and it is essential for students of knowledge. On the other hand, mental maps are considered one of the modern education methods where we express ideas through diagrams using pictures, symbols and colors instead of being limited to words only, so we link the meanings of words with pictures, and connect different meanings to each other. Consequently, in our research paper, we aim to highlight the role of mental maps as an aid to learning the science of grammar and to familiarize themselves with its rules, taking the board of al-Ajrumiyya by Ibn Ajrum as an applied example.